2012
DOI: 10.6002/ect.2012.0083
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Liver Transplant Graft-Versus-Host Disease With Antibodies Against Tumor Necrosis Factor-α

Abstract: Acute graft-versus-host disease is uncommon after liver transplant. We recently treated a 60-year-old man with liver transplant for hepatocellular carcinoma. After the primary liver transplant graft did not function, revision liver transplant resulted in excellent function. Subsequently, the patient developed watery diarrhea, systemic inflammatory response syndrome, a skin rash on his limbs and trunk, and palmar erythema. Skin biopsy suggested viral exanthems consistent with cytomegalovirus. Despite treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…In 61 cases (60.4%), sepsis was documented as cause of death. The causative organism was reported in 25 cases (41%); invasive aspergillosis was noted in 9 cases 1, 9, 1217 (36%), disseminated candidiasis in 7 (28%) (3 albicans , 1 kruseii , 1 glabrata and 2 unspecified species) 1, 9, 18, 19 , enterococci in 7 (28%) 1, 2023 and Enterobacter in 2 (8%) 1, 24 .…”
Section: Resultsmentioning
confidence: 99%
“…In 61 cases (60.4%), sepsis was documented as cause of death. The causative organism was reported in 25 cases (41%); invasive aspergillosis was noted in 9 cases 1, 9, 1217 (36%), disseminated candidiasis in 7 (28%) (3 albicans , 1 kruseii , 1 glabrata and 2 unspecified species) 1, 9, 18, 19 , enterococci in 7 (28%) 1, 2023 and Enterobacter in 2 (8%) 1, 24 .…”
Section: Resultsmentioning
confidence: 99%
“…Concern for cutaneous GVHD should prompt further evaluation of other organs for GVHD. Though there is no consensus treatment for GVHD following SOT, tumor necrosis factor- α inhibitors and T-cell depleting antibodies are encouraging therapeutic options [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…One patient was given TNF inhibitors and anti‐IL2R inhibitors and is alive 2 years after transplant. Similarly, for the 4 patients reported in the literature to have had TNF‐α–inhibition treatment, the reported survival rate was high (75%) . The 2 other patients from our series who received mAb treatment died from GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…Duplicates excluded were the reports by Kuball et al (Schuchmann et al reported their patient ), by Sudhindran et al and Taylor et al (Key et al had described their patients ), and by Neumann et al (Kohler et al had previously published their patient ). A total of 78 studies were withheld, in which a total of 150 patients with LTx‐associated GVHD were identified …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation